Grandchild of the NBAS: The NICU Network Neurobehavioral Scale (NNNS): A Review of the Research Using the NNNS. Issue 3 (4th August 2013) - Tronick, Ed; Lester, Barry M.
Abstract : A review of the research on the NICU Network Neurobehavioral Scale (NNNS) is presented. The NNNS has good psychometric properties and reliability. Standardized norms are available for it. It was found to be sensitive to a wide variety of medical, exposure, and demographic variables and has robust predictive validity. It will be useful for nurses for detecting neurobehavioral problems and management of the young infant.